No “Over”, Yes “Minimal”! Camp and Caravan Tourism - Bilim, Yasin; Özer, Özgür (Anais Brasileiros de Estudos Turísticos, 2021)
Last developments show that over-population, modern life and physical or mental health problems have steered the people to nature and isolated areas. It will be understood that camp and caravan tourism offers exciting experiences which demonstrate the value of the nature gives the chance to learn living with limited minimal conditions and especially provide secure tourism activities alternatively to current Covid-19 pandemic period negative tourism developments. The study aims to show how camp and caravan tourism can be an alternative for modern people insisting on sustainable and healthy tourism activities with social distance and isolated living instead of huge hedonic, unnecessary, luxury consumption and crowd living spaces. The study has constructed on a theoretical approach based on literature review and to support the theories web-based observational and hermeneutic analysis have been hold. Some potential geographies like Latin America and Europe have been selected to explain the contribution of camp and caravan tourism. Key words: Camp and Caravan Tourism; Sustainability; Environmental Sensitivity; Covid-19 Pandemic.